2010
DOI: 10.1590/s0102-311x2010001000012
|View full text |Cite
|
Sign up to set email alerts
|

Early determinants of attention and hyperactivity problems in adolescents: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study

Abstract: The aim of this study was to assess early determinants of attention and hyperactivity problems in adolescents. In 1993, all hospital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
19
0
7
Order By: Relevance
“…The prevalence of ADHD and respective 95% CI was calculated for the entire cohort and separately by sex (based on the current literature that consistently reports higher prevalence rates among boys) 5–13. The association between maternal caffeine consumption grouped in three categories <100, 100–299 and ≥300 mg/day and ADHD was evaluated by means of the χ 2 test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of ADHD and respective 95% CI was calculated for the entire cohort and separately by sex (based on the current literature that consistently reports higher prevalence rates among boys) 5–13. The association between maternal caffeine consumption grouped in three categories <100, 100–299 and ≥300 mg/day and ADHD was evaluated by means of the χ 2 test.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have shown higher prevalence among boys and among children belonging to families with worse socioeconomic conditions 5–13. Maternal caffeine consumption14 as well as other nutritional factors during pregnancy, such as intake of folic acid,15 iron16 and omega-317 have been investigated as determinants of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…In studies in Brazil, the estimates of ADHD prevalence in children and adolescents range from 5.8% to 19.9%, and vary depending on the diagnostic criteria used and the type of sample analyzed [8][9][10][11] . ADHD often persists beyond adolescence into adulthood, although the presentation of symptoms differs between adults, children, and adolescents 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Muitos autores concordam que a prevalência de transtornos específicos, bem como possíveis fatores de risco e de proteção variam entre as culturas e entre os diversos contextos socioeconômicos (Lund et al, 2010;Lund et al, 2011;Canino & Alegría, 2008;Hackett & Hackett, 1999, Roberts et al, 1998 problemas comportamentais e de saúde mental e idade paterna ; renda familiar (Anselmi et al, 2010), baixo nível socioeconômico (Prior et al, 2005) e tipo de escola (Syed et al, 2007). Lund et al (2010) e Lund et al (2011 verificaram com base em estudo de revisão que, dos 115 estudos analisados, 79% deles relataram associação positiva entre transtornos mentais comuns e alguma medida de pobreza, apontando que as condições sociais e econômicas estão associadas ao aumento destes transtornos em países de baixa e média renda.…”
Section: Associação Entre Aspectos Cognitivos Comportamentais E Emocunclassified
“…Nestes estudos específicos, as taxas de prevalência de problemas mentais foram menores, enquanto que nos estudos de coorte brasileiros mencionados (Gallo et al, 2011;Silva et al, 2011;Anselmi et al 2010), incluindo o presente estudo, as taxas de prevalências foram maiores. Vale ainda o apontamento que em estudos de coorte um grupo de indivíduos compartilha as mesmas experiências culturais e históricos e é avaliado dentro de uma faixa estreita de tempo.…”
Section: Associação Entre Aspectos Cognitivos Comportamentais E Emocunclassified